Clinical spectrum of Cutibacterium acnes infections: The SAPHO syndrome - Michaele Francesco Corbisiero; Nisha Batta; Hannah Kyllo; Anthony Smyth; Lorna Allen; Carlos Franco-Paredes (IDCases, 2023)
Cutibacterium acnes, previously known as Proprionobacterium, is a commensal Grampositive bacterium of the skin commonly implicated in prosthetic joint infections. However, it has been documented to play a role in other conditions, including SAPHO syndrome (synovitis, acne, pustulosis, hyperostosis, osteitis), a rare autoinflammatory disorder. Diagnosing SAPHO syndrome is cumbersome, as the clinical manifestations are variable and overlap with many inflammatory joint disorders. Herein, we describe a 56-year-old female patient with a presumed diagnosis of longstanding seronegative rheumatoid arthritis and history of C. acnes prosthetic joint infection following revision arthroplasty of the right shoulder. She presented to our clinic with a rash over the upper extremities and trunk and joint symptoms involving the right shoulder. Treatment was initiated with ceftriaxone followed by doxycycline suppressive therapy, with clinical improvement of joint and skin involvement. Symptoms recurred upon brief cessation of antibiotic therapy due to adverse gastrointestinal effects; however, symptoms abated once again upon re-initiation of treatment. Given the patient’s cutaneous lesions and longstanding history of arthritis that improved with antimicrobial therapy against C. acnes, the diagnosis of SAPHO syndrome was entertained. The present case demonstrates the clinical challenges of diagnosing SAPHO syndrome and the importance of its consideration on the differential for a patient with osteoarticular and cutaneous features. Additional literature is needed to improve diagnostic criteria and treatment guidelines.